Co-Designing Team Design Patterns for Integration of New Technologies in USAR Operations - van Koningsveld, Mark; van Tuijn, Rosa; Haije, Tjalling; Neerincx, Mark (Proceedings of the International ISCRAM Conference, 2026)
Emerging technologies such as drones, wearables, robots, and AI offer clear potential for improving safety and situational awareness in Urban Search and Rescue (USAR), but their integration into practice remains difficult in multi-stakeholder projects. This Work-in-Progress paper presents an iterative co-design approach, structured by Socio-Cognitive Engineering (SCE), to derive Use Cases, Team Design Patterns (TDPs) and Interaction Design Patterns (IDPs) for USAR operations. Over multiple stakeholder sessions during field-test events, interviews, focus groups, observations, and evolving design artefacts were combined to elicit operational needs, role divisions, information requirements, and autonomy boundaries. These inputs were translated into representative use cases and an initial set of USAR-specific TDPs and IDPs. The current results should be seen as a stakeholder-informed baseline rather than field-validated design knowledge, but they already offer reusable guidance for coordination, information routing, and human–technology collaboration in high-risk operations.